The socio-economic essence of women’s entrepreneurship, its development factors, and its institutional significance in the modern economic system. - Saodat Ikromovna Bekmurodova (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This scientific study analyzes the role and significance of women’s entrepreneurship in ensuring the sustainable development of the national economy. Within the framework of the research, the contribution of women’s entrepreneurship to expanding employment, reducing poverty, mitigating social inequality, and enhancing resilience to economic crises is substantiated on a scientific basis. Furthermore, the effectiveness of state policies, regulatory and institutional mechanisms aimed at stimulating women’s economic activity - including organizations supporting women’s entrepreneurship, targeted lending instruments, and business education programs - is assessed. The research findings demonstrate that the development of women’s entrepreneurship is a crucial factor in promoting inclusive economic growth, increasing long-term competitiveness, and strengthening gender equality.